Respiratory rehabilitation for patients with COVID-19 infection and chronic respiratory failure: a real-life retrospective study by a Lombard network - Vitacca, Michele; Salvi, Beatrice; Lazzeri, Marta; Zampogna, Elisabetta; Piaggi, Giancarlo; Ceriana, Piero; Cirio, Serena; Rizzello, Luigino; Lacala, Grazia; Longoni, Angelo; et al. (Monaldi Archives for Chest Disease, 2021)
The Lombardy region has been one of the areas most affected by the COVID-19 pandemic since the first months of 2020, providing real-life experiences in the acute phase. It is unclear how the respiratory rehabilitation network responded to this emergency. The aims of this retrospective study were: i) to analyze clinical, functional, and disability data at admission; ii) describe assessment tools and rehabilitative programs; iii) evaluate improvement after rehabilitation. The study was conducted on data collected from ten pulmonary rehabilitation centers in Lombardy, between the period of March 1st 2020 to March 1st 2021, in patients with respiratory failure recovering from COVID-19 both at admission and discharge. The study included demographics, comorbidities, nutritional status, risk of falls, disability status (Barthel index; Short Physical Performance Battery (SPPB); 6 minutes walking test (6MWT), symptoms (dyspnoea with Barthel Dyspnoea and MRC Dyspnoea Scale), length of stay, discharge destination, need for mechanical ventilation, respiratory function, assessment/outcomes indices, and prescribed rehabilitative programs. 413 patients were analyzed. Length of stay in acute and rehabilitative units was less than 30 days. Fifty % of patients used non-invasive ventilation during their stay. Functional status was mildly compromised for forced volumes and oxygenation, while severely compromised for diffusion capacity. Independency was low while physical performance status very low. At discharge, 318 (77%) patients were sent home, 83 (20.1%) were transferred to an acute unit and 12 (2.9%) passed away. Barthel Index and 6MWT were the most used, while MRC score was the least used outcome parameter. The 5 main rehabilitative activities were walking (90.8 %), transfer from bed to armchair (77.5%), limb mobilization in bed (76%), balance (71.2%), and cycle-ergometer or treadmill (43.1%). A huge difference was found in admission, discharge, and delta change among different rehabilitative centers. When available, all outcomes showed a significant improvement. With the limitation of a retrospective study with a clear amount of missing data, COVID-19 subjects admitted to rehabilitative centers presented a reduced physical performance, symptoms of dyspnoea, and severe disability. The 6MWT and Barthel index were the most used measurement.